АСЕАН в контурах торговельної взаємозалежності: парадокси інтеграційної взаємодії - Резнікова, Н.В. (Культура народов Причерноморья, 2013)
В центрі уваги опинився аналіз торговельної інтеграції де-факто й торговельної інтеграції
де-юре в межах, яка відноситься до свідомої політики держав, спрямованої на координацію
торговельної діяльності в конкретному регіоні. В статі розглядається роль Угод про вільну торгівлю в
поглибленні торговельної інтеграції де-юре в АСЕАН. Доведено, що торговельна взаємозалежність між
КНР і АСЕАН є відносно незначною і фактично скорочується. Порівняння різних показників репрезентує
особливості нещодавнього розвитку торговельної взаємозалежності в рамках АСЕАН.
Ключові слова. Торговельна взаємозалежність, АСЕАН, угода про вільну торгівлю, внутрішньо-
регіональна торгівля. В центре внимания оказался анализ торговой интеграции де-факто и торговая интеграция
де-юре, которая относится к сознательной политике государств, направленной на координацию
торговой деятельности в конкретном регионе. В статье рассматривается роль соглашений о
свободной торговле в углублении торговой интеграции де-юре в АСЕАН. Доказано, что торговая
взаимозависимость между КНР и АСЕАН является относительно незначительной и фактически
сокращается. Сравнение различных показателей демонстрирует особенности развития торговой
взаимозависимости в рамках АСЕАН.
Ключевые слова. Торговая взаимозависимость, АСЕАН, соглашение о свободной торговле, внутри-
региональная торговля. It is necessary to study the relative scales of the trade creation effect and the trade diversion effect to
evaluate success of ASEAN trade integration. The Association of Southeast Asian Nations (ASEAN) was formed
in 1967 by Indonesia, Malaysia, Philippines, Thailand and Singapore, joined by Brunei in the 1980s (known as
ASEAN-6), and by Cambodia, Laos, Myanmar and Vietnam (known as CLMV) in the 1990s. The ASEAN-10
members are diverse in size, level of economic development, resource endowment, and industrial and
technological capabilities. In addition, ASEAN has in place a services liberalisation agreement and an
investment liberalisation agreement. ASEAN is also forging FTAs with China, Japan, South Korea and India,
while individual ASEAN countries are forming bilateral FTAs with a growing number of countries in the Asia
Pacific and beyond. Free Trade Agreements (FTAs) aim to reduce or eliminate trade barriers between the
parties to the FTAs, and thus increase trade between them. An FTA also provides legal certainty or “insurance”
in that it prevents a party to the FTA from unilaterally increasing trade barriers vis-à-vis its FTA partner.
Furthermore, FTAs of a good quality help to keep up the momentum of free trade and act as building blocks to
greater regional or international trade liberalisation. Given these advantages, FTAs have been a crucial
component of ASEAN’s trade strategy over the past three decades. We assume, that consequently, intraregional
trade increased to a greater extent than extraregional trade. ASEAN is a good example for a successful export
based development strategy. Although its member states integrated their economies to a free trade area, their
major economic partners are outside the regional integration organization.
Key words: Trade interdependence, ASEAN, free trade agreement, intra-regional trade.